Screening of long non-coding RNAs markers in plasma of children with chronic gastritis - Zhen Gu (KeAi Communications Co., Ltd., 2020)
Objective: The study aimed to detect and analyze long non-coding RNAs (lncRNAs) in plasma of children diagnosed with chronic gastritis, and to explore its biological functions and involved signaling pathways. Methods: The plasma samples were collected from six children that were diagnosed with chronic gastritis by physical examination, gastroscopy, and pathological examination and six healthy children. The plasma samples were assayed for determining the expression profiles of lncRNA based upon the gen chip detection. The specific expression of lcnRNA in plasma of children with chronic gastritis was analyzed and its biological functions were speculated. Results: Five lncRNAs (RP11-697M17.1, RP11-388M20.9, AFAP1-AS1, BC062758, and XLOC001406) were significantly up-regulated, and five lncRNAs (UNQ697, BX571672.5, CYP4F35P, ANKRD20A5P, and AL832737) were observed to be significantly down-regulated. The lncRNAs RP11-697M17.1, and UNQ697 were detected with the highest up-regulation and down-regulation, respectively. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that the up-regulated lncRNAs were significantly enriched in 20 signaling pathways such as phosphoinositide-3-kinase–protein kinase B (PI3K-Akt) pathway, and the down-regulated lncRNAs target genes were significantly enriched in 20 signaling pathways such as the metabolic pathway. Conclusion: The analysis of the lncRNA expression profiles in plasma of children with chronic gastritis revealed that the lncRNA RP11-697M17.1, and lncRNA UNQ697 may act as plasma markers for predicting chronic gastritis in children. Keywords: RP11-697M17.1, UNQ697, Chronic gastritis, Plasma markers